Activity-Dependent Plasticity and Gene Expression Modifications in the Adult CNS - Carulli, Daniela; Foscarin, Simona; Rossi, Ferdinando (Frontiers in Molecular Neuroscience, 2011)
Information processing, memory formation or functional recovery after nervous system damage depend on the ability of neurons to modify their functional properties or their connections. At the cellular/molecular level, structural modifications of neural circuits are finely regulated by intrinsic neuronal properties and growth-regulatory cues in the extracellular milieu. Recently, it has become clear that stimuli coming from the external world, which comprise sensory inflow, motor activity, cognitive elaboration or social interaction, not only provide the involved neurons with instructive information needed to shape connection patterns to sustain adaptive function, but also exert a powerful influence on intrinsic and extrinsic growth-related mechanisms, so to create permissive conditions for neuritic remodelling. Here, we present an overview of recent findings concerning the effects of experience on molecular mechanisms underlying CNS structural plasticity, both in physiological conditions and after damage, with particular focus on activity-dependent modulation of growth-regulatory genes and epigenetic modifications.